THE REGULATORY FRAMES AND MODELS OF SELF-DRIVING CARS - Juhász, Ágnes (Zbornik radova Pravnog fakulteta u Novom Sadu, 2019)
Until the recent years, it seemed so futuristic that the time would come, when no drivers would be needed, but the cars would drive themselves. Today, the existence of the so-called self-driving cars (in other words autonomous or automated cars) and their participation in road transport is reality, and that raises numberless legal and ethical questions. The study reviews the regulatory frames of these vehicles from several point of view: after the introduction of the international rules on road traffic, attention is given to the current legal provisions adopted in certain states of the USA, since these states were the first in the word, who attempted to create the legal basics for self-driving cars. After the reviewing of the selected American rules, the main tendencies of the actual and future European regulation will be presented. Among the European states, the German regulation amended in 2017 will be examined in details. Nevertheless, the recent regulatory tendencies of other countries (e.g. Hungary) will be reviewed as well.